Physical Activity, Sleep Quality, Screen Time, Peer Support and Physical Fitness in Fifth Grade Elementary Students - Ahmad Fajar Kurniawan; Aris Fajar Pambudi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study examined the associations of physical activity, sleep quality, screen time, and peer support with physical fitness among fifth grade students at SD Negeri Klodangan. A quantitative correlational design with a cross sectional approach was employed. Participants were 28 fifth grade students (12 boys and 16 girls). Physical fitness was assessed using a test battery consisting of the 20 m PACER, 30 second curl up, 30 second push up, standing long jump, sit and reach, and the 10×5 shuttle run. Physical activity and screen time were collected through a weekly journal, sleep quality was measured using a questionnaire, and peer support was assessed using a rating scale. Data were analyzed using descriptive statistics, assumption tests, Pearson or Spearman correlation, and multiple linear regression. The results indicated that physical activity, sleep quality, screen time, and peer support were not significantly correlated with physical fitness (p > 0.05), with Spearman correlation coefficients ranging from −0.220 to 0.256. Multiple regression also showed no significant simultaneous effect (R² = 0.160; p = 0.384). In conclusion, variations in students’ physical fitness in this context may be influenced by other factors beyond the proposed model. Further research is recommended to consider nutritional status, structured exercise intensity, and students’ motivation for physical activity.